Cooperative leadership as a condition for patient-reported rehabilitation success - Meyer, Thorsten; Kleineke, Vera; Stamer, Maren (Frontiers in Rehabilitation Sciences, 2023)
Rehabilitation is a complex intervention in a complex setting. The MeeR-project (characteristics of successful rehabilitation facilities) aims to identify complex conditions of successful rehabilitation outcomes. A project with a sequential mixed-methods study design (quantitative pre-study and qualitative main study) was applied. Based on a league-table of case-mix-adjusted quality assurance outcome data k=6 rehabilitation facilities (orthopaedic and cardiac rehabilitation centres) were recruited based on the results of the quantitative analysis: 3 facilities that ranked top 10%, 3 facilities that ranked lowest 10% of the adjusted league-table. All 6 rehabilitation facilities were visited each for one week by two researchers. We conducted participant observations, expert interviews with medical and administrative leaders, group discussions with rehab team members, and group discussions with patients. Subsequently, a systematic comparison of the results of the upper and lower 10% facilities was conducted to identify those characteristics that distinguished those institutions from one another. One of the three clusters of characteristics that distinguished the above and below 10% facilities related to team-work or interdisciplinary cooperation: among others, the extent of interdisciplinary cooperation was higher in the rehabilitation facilities with higher degree of success, the leading medical doctors were less dominant in these institutions, and there was also a more comprehensive representation of the team within team meetings, i.e. the quality and amount of interdisciplinary cooperation was higher in these institutions compared to rehabilitation facilities with lower level of success. This project provided qualitative evidence for the role of interdisciplinary cooperation and collaborative leadership and its different facets for a patient-related successful rehabilitation. It provides valuable insights into the fabrics and structure of a rehabilitation institution and a variety of target points for team development and group leading interventions.